NONTHERMAL PLASMA: A REVIEW ON ITS PROSPECTS ON FOOD PROCESSING - Arda, Gede; Hsu, Chuan Liang (The University of Lampung, 2020)
Corrigendum to: NONTHERMAL PLASMA: A REVIEW ON ITS PROSPECTS ON FOOD PROCESSING